2019
DOI: 10.1080/1359432x.2019.1602041
|View full text |Cite
|
Sign up to set email alerts
|

Manifesto for the future of work and organizational psychology

Abstract: This manifesto presents 10 recommendations for a sustainable future for the field of Work and Organizational Psychology. The manifesto is the result of an emerging movement around the Future of WOP (see www. futureofwop.com), which aims to bring together WOP-scholars committed to actively contribute to building a better future for our field. Our recommendations are intended to support both individuals and collectives to become actively engaged in co-creating the future of WOP together with us. Therefore, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 30 publications
1
54
0
8
Order By: Relevance
“…For example, a recent study among graduate students (90% of which were PhD students) in 26 countries across 234 institutions showed that graduate students "are more than six times as likely to experience depression and anxiety as compared to the general population" [35]. Our study suggests that prolonged publishing times are likely to contribute to this "health crisis in academia" [16].…”
Section: Discussion Of the Empirical Studymentioning
confidence: 64%
See 1 more Smart Citation
“…For example, a recent study among graduate students (90% of which were PhD students) in 26 countries across 234 institutions showed that graduate students "are more than six times as likely to experience depression and anxiety as compared to the general population" [35]. Our study suggests that prolonged publishing times are likely to contribute to this "health crisis in academia" [16].…”
Section: Discussion Of the Empirical Studymentioning
confidence: 64%
“…Second, we address why, despite its problems and many criticisms, the current journal-based publication system is so persistent by arguing and showing that tenured researchers tend to be less dissatisfied with the current publication system compared to untenured researchers. Third, there has been very little reflection among Work and Organizational Psychology (WOP) researchers about cognitive alternatives for the current publication system [16]. Rather than proposing some incremental changes, we envision what an alternative publication system for (WOP) research could look like.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent study among graduate students (90% of which were PhD students) in 26 countries across 234 institutions showed that graduate students "are more than six times as likely to experience depression and anxiety as compared to the general population" [32]. Our study suggests that prolonged publishing times are likely to contribute to this "health crisis in academia" [14].…”
Section: Discussion Of the Empirical Studymentioning
confidence: 67%
“…Second, we address why, despite its problems and the many criticisms, the current journal-based publication system is so persistent by arguing and showing that tenured researchers tend to be less dissatisfied with the current publication system compared to untenured researchers. Third, there has been very little reflection among (WOP) researchers about cognitive alternatives for the current publication system [14]. Rather than proposing some incremental changes, we envision what an alternative publication system for (WOP) research could look like.…”
Section: Introductionmentioning
confidence: 99%
“…Se han revisado diversas cartas y manifiestos sobre psicología (Bal et al, 2019;Mc Fall, 1991;Merani, 1980;The British Psychological Society, 2019;Valsiner et al, 2016;Watt, 1995) y salud mental (Kinderman, 2019) antes de construir el presente Manifiesto por la Psicología en Chile para que, aunque respondiendo principalmente a la realidad de nuestro país, pueda también ser de utilidad y permita la discusión en otros países latinoamericanos.…”
Section: Manifiesto Por La Psicología En Chileunclassified